1987
DOI: 10.1128/mcb.7.11.4030
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of the U1 small nuclear ribonucleoprotein particle.

Abstract: Although the Ul small nuclear ribonucleoprotein particle (snRNP) was the first mRNA-splicing cofactor to be identified, the manner in which it functions in splicing is not precisely understood. Among the information required to understand how Ul snRNP participates in splicing, it will be necessary to know its structure. Here we describe the in vitro reconstitution of a particle that possesses the properties of native Ul snRNP. 32P-labeled Ul RNA was transcribed from an SP6 promoter-human Ul gene clone and incu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
90
0

Year Published

1989
1989
2003
2003

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(96 citation statements)
references
References 44 publications
(43 reference statements)
6
90
0
Order By: Relevance
“…The secondary structure, but not the sequence, of this stem loop is conserved. Interestingly, deletion of the terminal stem of U1 produced a stable RNA in Xenopus oocytes that was not Sm-precipitable (Jarmolowski and Mattaj 1993), whereas deletion of the terminal stem loop in HeLa extracts altered the sedimentation behavior of the resulting U1 particles (Patton et al 1987). Here, we observed that several phosphates within the terminal stem loop of U1 significantly affect RNP stability when changed to phosphorothioates.…”
Section: A Stem-loop Clamp For the Sm Ringmentioning
confidence: 52%
“…The secondary structure, but not the sequence, of this stem loop is conserved. Interestingly, deletion of the terminal stem of U1 produced a stable RNA in Xenopus oocytes that was not Sm-precipitable (Jarmolowski and Mattaj 1993), whereas deletion of the terminal stem loop in HeLa extracts altered the sedimentation behavior of the resulting U1 particles (Patton et al 1987). Here, we observed that several phosphates within the terminal stem loop of U1 significantly affect RNP stability when changed to phosphorothioates.…”
Section: A Stem-loop Clamp For the Sm Ringmentioning
confidence: 52%
“…There are many examples of reconstitution of snRNPs using X. laevis egg extracts or HeLa cell S100 extracts IHamm et al 1987IHamm et al , 1988Patton et al 1987;Patton and Pederson 1988;Kleinschmidt et al 1989;Pikielny et al 1989) and examples of functional assembly of human snRNA with amphibian or HeLa proteins (Krainer 1988;Pan and Prives 1988). This work and that of McPheeters et al (1989) are the first examples of synthetic U-RNAs that are able to restore splicing in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Transcription of the human Ul RNA gene clone pHUI, assembly of Ul snRNP in a HeLa SIO fraction, and glycerol gradient purification were carried out as previously described (26,27 …”
Section: Methodsmentioning
confidence: 99%